Faculty and staff members. - Unknown:::Creator::::::::::::
Written on verso: "Janitors 1915, 1916 or 1919; Upper: J. Eckhardt (Engineer), Frank Adams (Janitor), J.P. Stillwell (Head Janitor); Lower: Frank Emser (Watchman), Tom Hollingsworth (Gardner), Student Watchman."